CALENDAR ANOMALIES OF JANUARY EFFECT, DAY OF THE WEEK EFFECT AND SIZE EFFECT TOWARD STOCK RETURN ON GO PUBLIC COMPANY LISTED INDONESIA STOCK EXCHANGE PERIOD 2013 â€“ 2017 - Aprilia, Nanda B1024141010 (Jurnal Manajemen Update, 2019)
An efficient capital market hypothesis says that markets that efficiently react quickly to relevant information. In an efficient market, the market will quickly react to new information coming in so that a new equilibrium price will be reached quickly. In practice in the capital market phenomena appear that show deviations that are contrary to the concept of efficient capital markets (market anomaly). The pupose of this research to investors becauseÂ  Investors need information to assess the risks involved in their investments and to estimate returns on the investment. With the information obtained, investors can determine the position of selling, buying or holding a stock. These anomalies including the January Effect, Day of The Week Effect and Size Effect.The data used in this study are secondary data from companies listed on the Indonesia Stock Exchange during the study period from January 2013 to December 2017. The samples used in this study were 55 issuers with purposive sampling method. The statistical analysis used in this study is by multiple regression analysis with dummy variables for January effects and Day of The Week effect while different T tests for firm size effects.The results of hypothesis testing with multiple linear regression analysis with Independent variables, namely January Efeect, Day Of The Week Effect, and Size Effect and Dependent variables namely Stock Return. Based on the results of multiple linear regression test analysis using dummy variables showing that the January Effect of each variable has a significant influence on Stock return and on the day of the week effect on Monday, Tuesday, Wednesday, Thursday and Â Friday also has a significant effect on stock returns. While the size effet based on the results of the independent t-test on the size effect variable of a company has a significant effect (<0.05) which means that the size of a company has an impact on a company's stock return, where the company is measured based on total asset.Â REFERENCESÂ Ahmad, Z dan Simon Hussain, 2001, â€œKLSE Long Run Overreaction and The Chinese New Year Effectâ€, Journal of Business Finance and Accounting, Vol 28, p.1-2Ang, Robert, 2000, Buku Pintar Pasar Modal Indonesia (The Intelligent Guid to Indonesian Capital Market), Mediasoft Indonesia.Banz, R., 1981, â€œThe Relationship Between Return and Market Value of Common Stockâ€, Journal of Financial Economic, 9: 3-18.Balaban, E., Bayar, A., and Kan, Ã–., 2001, Stock returns, seasonality and asymmetric conditional volatility in world equity markets, Applied Economics Letters 8, 262-268.Berument, H., and Kiymaz H., 2001, The day of the week effect on stock market volatility, Journal of Economics and Finance 25, 181-194.Berument, H., and Kiymaz, H.,., 2003, The day of the week effect on stock market volatility and volume: International evidence, Review of Financial Economics 12, 363-381.Chatterjee, Amitava., 2000, â€œMarket Anomalies Revisitedâ€, Journal of Applied Business Research, vol: 13 No.4Choudhry, T., 2000, Day of the week effect in emerging Asian stock markets: evidence from the GARCH model, Applied Financial Economics 10, 235-242.Chotigeat, T and I.M. Pandey., 2005, â€œSeasonality In Asiaâ€™s Emerging Markets:India and Malaysia.â€, Internasional Trade and Finance Association. Paper 53Dyl, E. A. (1977). Capital Gains Taxation and Year-end Stock Market Behavior. Journal of Finance, 32, 165-75.Dubois, M., and Louvet, P., 1996, The day-of-the-week effect: The International Evidence, Journal of Banking and Finance 9, 1463-1484.Elton, Edwin J., and Gruber, Martin J., 1995, Modern Portfolio Theory and Investment Analysis, Fifth Edition, John Wiley & Sons, Inc.Fama, E. (1970). Efficient capital markets: A review of theory and empirical work. The Journal of Finance, 25 (2), 383-417.Fields, M. (1931). Stock Prices: A Problem in Verification. Journal of Business, 415-418. Fields, M. (1931). Stock Prices: A Problem in Verification. Journal of Business, 415-418.French, K. 1980. Stock Returns and the Weekend Effect. Journal of Financial Economics, 8, 55-69.French, Dan W and Trapani, Teresa D., 1994, â€œCash Balances and The January Effect in Stock Returnsâ€, Quarterly Journal of Business & Economic, Vol: 33 Iss:4 p: 3-12Ghozali, Imam., 2006, Analisis Multivariate Lanjutan Dengan Program SPSS, Badan Penerbit Universitas Diponegoro, Semarang.Gibbson, M.R. & Hess, P. (1981). Day of the week effects and asset returns. The journal of Business, 54(4), pp 579-596.Gumanti, Tatang Ary dan Elok Sri Utami., 2002, â€œBentuk Pasar Efisien dan Pengujiannyaâ€, Jurnal Akuntansi & Keuangan, Vol. 4, No.1, p54-66Haroon, M. A. & Shah, N. (2013). Investigating day of the week effect in stock returns: Evidence from Karachi Stock Exchange â€“ Pakistan. Pakistan Journal of Commerce and Social Sciences, 7 (2), 381-393.Hartono, Jogianto., 2000, Teori Portofolio dan Analisis Investasi, Edisi pertama, BPFE, JogjakartaHaugen R., and P. Jorion., 1966, â€œ The January Effect : Still There after ll These Years.â€ Financial Analyst Journal, vol:52:27-31.Henke, Harald., 2002, â€œTax-Loss Saelling and Window-Dressing: An Investigation of the January Effect in Poland.â€ Department of Economics. Eropa University Viadrina Frankfurt, Germany.Husnan, Suad. 2001, Dasar-Dasar Teori Portofolio dan Analisis Sekuritas, Edisi Ketiga, UPP AMP YKPN, YogyakartaHUSSAIN, Faryad; HAMID, Kashif; AKASH, Rana Shahid Imdad; KHAN, Majid Imdad. Day of the Week Effect and Stock Returns: Evidence from Karachi Stock Exchange-Pakistan. Far East Journal of Psychology and Business, V 3, N 1, April 2011.Jaffe, J., and Westerfield, R., 1985, The week-end effect in common stock returns: the international evidence, Journal of Finance 40, 433-454.Jabareen, Y. (2009). Building a Conceptual Framework: Philosophy, Definitions, and Procedure. International Journal of Qualitative Methods, 8(4)Jones, C.P., 2000, Investments: Analysis and Management, 7th ed., New York, NY:John Wiley & Sons, Inc.Keim & Donald B. (1983). Size-related anomalies and stock return seasonality: Further empirical evidence. Journal of Financial Economics, 12(1), 13-32.Kingâ€™ori, E.N. (2005). Stock Market Seasonalities at the Nairobi Stock Exchange. University of Nairobi. Unpublished MBA ProjectKohers, G., Kohers, N., Pandey, V., and Kohers, T., 2004, The disappearing day-of-the-week effect in the worldâ€™s largest equity markets, Applied Economics Letters 11, 167-171.Lamoureux, Christopher G., and Sanger, Gary C., 1989. â€œFirm Size and Turn-ofthe-Year Effects in the OTC / NASDAQ Marketâ€, The Journal of Finance, Vol XLIV No. (5).Lakonishok.J. & Levi. M. (1982).Weekend Effects on Stock Returns: A Note. The Journal of finance, 37(3), 883â€“889. DOI: 10.1111/j.1540-6261.1982.tb02231.x.Li, Eng Li., 1998, â€œTiming Stock Purchase and Sales in Kuala Lumpur, Mumbai, Singapore and Bangkok.â€ Singapore Management Review. Vol:20 Iss:1p:65-67Ondiala, M. O. (2014). The turn of the month effect at the Nairobi Securities Exchange. Unpublished MSc. Finance Research Project, University of Nairobi.Pearce, Douglas K., 1955, â€œThe Robustness of Calendar Anomalies in Daily Stock Returns.â€ College of Management North Carolina State University. FReilly, F.K. & Brown, K.C., (2003). Investment Analysis and Portfolio Management. Mason, Ohio: South-Western/Thomson Learning.Ritter J., and N.Chopra., 1989,â€Portofolio Rebalancing and the Turn of the Year Effectâ€, Journal of Finance 44: 149-166.Reinganum, Marc R., 1992, â€œA Revival of the Smal-Firm Effectâ€. Journal of Portofolio Management, Vol:18 Iss:3 p:55-62.Ritter, Jay R dan Ziemba, William T., 1988,â€ The Buying and Selling Behaviour of Individual Investor at the Turn of the Yearâ€, Journal of Finance, Vol:43 Iss:3 p:701-719Robert A. Haugen dan Philippe Jorion., 1996, â€œThe January Effect: Still There after All These Yearsâ€, Financial Analyst Journal, January-FebruaryRozeff, M. S. & Kinney, W. R.(1976). Capital Market Seasonality: The Case of Stock Returns. Journal of Financial Economics, 3, 379-402.Rathinasamy, R.S dan Krishna G. Mantripragada., 1996, â€œThe January Size Effect Revisited: Is it A Case of Risk Mismeasurement?â€ Journal of Financial and Strategic Decisions. Vol:9 No. 3R. Christie-David and M. Chaudhry., 2000, â€œJanuary Anomalies: Implications for the Marketâ€™s Incorporation of Newsâ€, The Financial review, Vol:3 p.79-96Santoso, Singgih., 2004, SPSS Versi 10: Mengolah Data Statistik Secara Profesional, PT. Elex Media Komputindo, Jakarta.Sharpe, W.F., Alexander, G.J, and Bailey, J.V., 1995, Investments, Fifth Edition, Prentice Hall, New Jersey.Strong, N. (1992). Modeling Abnormal Return: A review article. Journal of Business Finance and Accounting, 19 (4), 533-553.Suryawijaya, Marwan Asri dan Faisal Arief Setiawan. 1998, â€œReaksi Pasar Modal Indonesia Terhadap Peristiwa Politik Dalam Negeriâ€, Kelola, No. 18/VIIWong, M. K., Ho, C. M., Dollery, B. (2007). An Empirical Analysis of the Anomalous Stock Market Behavior of Small Firms in January: Empirical Test for Year-End Tax Effect. University of New England.